The Volta Review (USA) - (:unkn) unknown (My University, 2026)
Congratulations to Dr Paris Binos, who has been appointed Associate Editor for AG Bell’s The Volta Review, a long-standing and well-recognised journal within the field of deafness and particularly early intervention for hearing loss. Paris will be involved in managing the review process for submitted manuscripts and providing guidance to authors and reviewers.